Implementasi Komunikasi Terapeutik Antara Perawat Dan Pasien Di Ruang Rawat Inap - Sri Sudarsih; Windu Santoso; Muhammad Hafidh Taqiuddin (STIKes YARSI Pontianak, 2025)
Background: Therapeutic communication is a very important element in nursing. Effective therapeutic communication is essential to foster trust and understanding between nurses and patients, which significantly improves patient care outcomes. Therapeutic communication skills are necessary for an effective therapeutic relationship. Objective: The objective of this research was to determine the implementation of therapeutic communication between nurses and patients. Method: The study is a descriptive study. The sample in the study were patients in the inpatient room, who were taken using purposive sampling techniques and in accordance with the researcher's criteria. Data collection used a Global Interprofessional Therapeutic Communication Scale (GITCS) instrument. Result: The results of the study showed that most of the nurses' therapeutic communication was in the good category. Conclusion: Most of the nurses' therapeutic communication is in the good category which is supported by 5 indicators, most of which are in the good category.